2021
DOI: 10.3390/mi12080921
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Elimination of Satellite Droplets during Monodisperse Droplet Generation by Using Piezoelectric Method

Abstract: One of the key questions in the generation of monodisperse droplets is how to eliminate satellite droplets. This paper investigates the formation and elimination of satellite droplets during the generation of monodisperse deionized water droplets based on a piezoelectric method. We estimated the effects of two crucial parameters—the pulse frequency for driving the piezoelectric transducer (PZT) tube and the volume flow rate of the pumping liquid—on the generation of monodisperse droplets of the expected size. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…A bipolar or unipolar signal is given as an input depending on the ink properties [86][87][88][89][90]. Experimental determination of optimal parameters is common, with rheology-dependent thresholds influencing droplet merging [91][92][93][94]. Bipolar waveforms are preferred for damping out vibrations, while unipolar waveforms offer stability with fewer satellites [95][96][97][98][99].…”
Section: Droplet Formation and Impactmentioning
confidence: 99%
“…A bipolar or unipolar signal is given as an input depending on the ink properties [86][87][88][89][90]. Experimental determination of optimal parameters is common, with rheology-dependent thresholds influencing droplet merging [91][92][93][94]. Bipolar waveforms are preferred for damping out vibrations, while unipolar waveforms offer stability with fewer satellites [95][96][97][98][99].…”
Section: Droplet Formation and Impactmentioning
confidence: 99%
“…Zejian Hu et al noted that, with an ink flow rate of 30 , increasing the pulse frequency from 10 to 30 caused previously split satellite droplets to merge with the main droplet. When the frequency reached 30 , the droplets appeared as uniformly sized single droplets [ 55 ]. When the pulse frequency is 40 , the ink droplets have irregular sizes.…”
Section: Inkjet Printing Quality Optimizationmentioning
confidence: 99%
“…Thirteen articles have been published after peer-review evaluations, and these articles cover a wide spectrum of active research in the frontiers of micro/nanosystems. For example, Hu et al [ 1 ] studied the satellite droplet generation in piezoelectric methods, and found that there are two key parameters responsible for this phenomenon: the pulse frequency for driving the piezoelectric transducer tube and the fluid flow rate. Optimal operation conditions have also been proposed to eliminate the satellite droplets for deionized water.…”
mentioning
confidence: 99%